2016
DOI: 10.1111/jsap.12495
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of cardiac injury and arrhythmias in dogs with acute kidney injury

Abstract: Acute kidney injury seems to be associated with cardiac injury and arrhythmias in dogs. The data do not indicate a cardiac cause of poor outcome in dogs with increased number of ventricular premature complexes but the association may reflect the severity of disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
(81 reference statements)
0
9
0
6
Order By: Relevance
“…A recent study has reported similar findings in dogs with acute kidney injury. 13 Accordingly, while primary cardiac disease should always be considered a potential cause of elevated serum troponins, it should not be thought of as the sole possible cause in dogs or cats with renal disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study has reported similar findings in dogs with acute kidney injury. 13 Accordingly, while primary cardiac disease should always be considered a potential cause of elevated serum troponins, it should not be thought of as the sole possible cause in dogs or cats with renal disease.…”
Section: Discussionmentioning
confidence: 99%
“…The codependence of the cardio–renal axis is well described, its interplay involving especially shared mechanisms related to volume and blood pressure regulation. 9,13 The so-called cardiorenal syndrome has been defined in humans, referring to pathological changes in one system ultimately affecting the other. 9,15 Chronic renocardiac syndrome is defined as ‘chronic abnormalities in renal function leading to cardiac disease’, 16 with causes including activation of the renin–angiotensin–aldosterone system and the sympathetic nervous system following a declining GFR, both of which induce cardiac remodelling with left ventricular hypertrophy (LVH) and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…ОПП является частым внутригоспитальным осложнением различных состояний, связанным с последующим формированием и прогрессированием ХБП, необходимостью применения заместительной почечной терапии, развитием сердечнососудистых и инфекционных осложнений и, в целом, существенным увеличением смертности таких пациентов [1][2][3][4]10]. Заболеваемость ОПП при аллогенной ТГСК является высокой [5-7, 13, 14], однако вопрос о том, насколько развитие ОПП может повлиять на исходы трансплантации, остается открытым из-за ограниченного числа исследований в этой области [15,16].…”
Section: Discussionunclassified
“…По данным N. Shingai и соавт. смертность больных после ТГСК в случае развития острой дисфункции почек в период до приживления трансплантата составила 39,1 % [16]. Нами было показано существенное увеличение смертности больных с ОПП в течение одного года после ТГСК по сравнению со смертностью пациентов без острой дисфункции почек.…”
Section: Discussionunclassified
“…CvRD K refere-se à disfunção cardiovascular que emana de um processo primário de doença renal (POUCHELON et al, 2015). Dentre as alterações que apresentam potenciais prejudiciais de CvRD K , incluem as anormalidades eletrolíticas, como a hipercalemia e hipocalemia que estão associadas as arritmias cardíacas (POUCHELON et al, 2015;KELLER et al, 2016;BAGSHAW et al, 2018); o uso de medicamentos que são utilizados para o tratamento das doenças cardiovasculares (digoxina, enalapril e atenolol) e que são excretados via renal provocando lesão renal primária, pois quando há disfunção renal e redução da depuração dos fármacos, ocorre o acúmulo das substâncias e sinais de toxicidade farmacológicas, além de desenvolver arritmias, hipotensão e piora da função miocárdica; distúrbios hemodinâmicos, como alterações de volume de fluido, que são sempre anormais em pacientes com doença renal grave e afetam o sistema cardiovascular devido ao baixo débito (POLZIN, 2011).…”
Section: Classificação Das Desordens Do Eixo Cardiovascular-renal Em unclassified